Deep sedation for transvenous lead extraction: a large single-centre experience. Issue 8 (18th May 2019) - Bode, Kerstin; Whittaker, Peter; Lucas, Johannes; Müssigbrodt, Andreas; Hindricks, Gerhard; Richter, Sergio; Doering, Michael
Abstract: Aims: Transvenous lead extraction for cardiac implantable electronic devices (CIED) is of growing importance. Nevertheless, the optimal anaesthetic approach, general anaesthesia vs. deep sedation (DS), remains unresolved. We describe our tertiary centre experience of the feasibility and safety of DS. Methods and results: Extraction procedures were performed in the electrophysiology (EP) laboratory by two experienced electrophysiologists. We used intravenous Fentanyl, Midazolam, and Propofol for DS. A stepwise approach with locking stylets, dilator sheaths, and mechanical sheaths via subclavian, femoral, or internal jugular venous access was utilized. Patient characteristics and procedural data were collected. Logistic regression models were used to identify parameters associated with sedation-related complications. Extraction of 476 leads (dwelling time/patient 88 ± 49 months, 30% ICD leads) was performed in 220 patients (64 ± 17 years, 80% male). Deep sedation was initiated with bolus administration of Fentanyl, Midazolam, and Propofol; mean doses 0.34 ± 0.12 μg/kg, 24.3 ± 6.8 μg/kg, and 0.26 ± 0.13 mg/kg, respectively. Deep sedation was maintained with continuous Propofol infusion (initial dose 3.7 ± 1.1 mg/kg/h; subsequently increased to 4.7 ± 1.2 mg/kg/h with 3.9 ± 2.6 adjustments) and boluses of Midazolam and Fentanyl as indicated. Sedation-related episodes of hypotension, requiring vasopressors, and hypoxia, requiring additional airway management, occurred in 25 (11.4%) and 5 (2.3%) patients, respectively. These were managed without adverse consequences. Five patients (2.3%) experienced major intraprocedural complications; there were no procedure-related deaths. All of our logistic regression models indicated intraprocedural support was associated with administration higher Fentanyl doses. Conclusion: Transvenous lead extraction under DS in the EP laboratory is a safe procedure with high success rates when performed by experienced staff.